2020
DOI: 10.3897/bdj.8.e57090
|View full text |Cite
|
Sign up to set email alerts
|

Detection and annotation of plant organs from digitised herbarium scans using deep learning

Abstract: As herbarium specimens are increasingly becoming digitised and accessible in online repositories, advanced computer vision techniques are being used to extract information from them. The presence of certain plant organs on herbarium sheets is useful information in various scientific contexts and automatic recognition of these organs will help mobilise such information. In our study, we use deep learning to detect plant organs on digitised herbarium specimens with Faster R-CNN. For our experiment, we manually a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 36 publications
0
14
0
3
Order By: Relevance
“…Their study trained a Faster R-CNN model and reported an accuracy of 95% on a sub-set of 61 test images. Similarly, Younis et al [ 30 ] proposed a Faster R-CNN model to detect and annotate different plant organs from digitized herbarium specimens. The authors manually annotated hundreds of images and used a subset of 498 images to train the model to detect different organs including flowers, leaf, fruit, seed, root, and stem.…”
Section: Related Workmentioning
confidence: 99%
“…Their study trained a Faster R-CNN model and reported an accuracy of 95% on a sub-set of 61 test images. Similarly, Younis et al [ 30 ] proposed a Faster R-CNN model to detect and annotate different plant organs from digitized herbarium specimens. The authors manually annotated hundreds of images and used a subset of 498 images to train the model to detect different organs including flowers, leaf, fruit, seed, root, and stem.…”
Section: Related Workmentioning
confidence: 99%
“…This means related datasets either focus on detecting entire plants or individual organs, such as leaves, from a singular plant species. Recently, a few small-scale plant organ detection approaches and datasets using more than one species have been developed, each using at most a few hundred herbarium sheets with the intended use of phenological information gathering [36,22,32]. In the context of species identification, these approaches are unable to collect data on present biodiversity and the geographical distribution of different plant species, an advantage that crowdsourcing initiatives possess.…”
Section: Related Workmentioning
confidence: 99%
“…Afonso et al., 2020; Buddha et al., 2019), detection of leaves and other plant organs on herbarium specimens (e.g. Ott et al., 2020; Weaver et al., 2020; Younis et al., 2020), stomata counting using microscopic leaf images (e.g. Fetter et al., 2019), animal counting using camera traps (Norouzzadeh et al., 2021) and many more.…”
Section: Introductionmentioning
confidence: 99%